NATIONAL IDENTITY: THE “WORLD OF GENERATIONS” AND THE “WORLD OF CONTEMPORARIES” - HARUTYUNYAN, EDVARD (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
The article deals with the problem of human identity and its architectonics. It is alleged that all identities are structured both horizontally and vertically, scilicet built on logic hierarchy. The past and future story of human life is a text of “how to live” in which we endlessly work and readjust according to our conceptions. In that sense, it is possible to say that every nation forms a special cultural system of life, within which the vertical (time) and the horizontal (spatial) identities of the nation are formed. These principles form a “world of contemporaries” in space and “world of generations” in time. The world organizing the national life is a “world of the community”, which is outstanding by its cultural power but not by its civilizational will, however, to address the challenges of the contemporary world a nation needs civilizational organization and a will to choose.
Keywords: culture of life, cultural identity, national identity, nаrrative identity, vertical identity, horizontal identity, nucleus of culture